Food Security and Climate Agenda - E. A. Maslova (Международная аналитика)
In the era of globalization and the global distribution of goods, including food, food security is not always adequately considered, especially in the so-called global North. This approach contrasts sharply with the climate agenda, which focuses on the existential side of food security. The Food and Agriculture Organization of the United Nations (FAO) reports that almost 12% of the world’s population is severely food insecure; 29% is moderately or severely food insecure; almost one in three people in the world (2.37 billion) do not have access to adequate nutrition, and the prevalence of malnutrition has reached 9.8% in 2021. These negative trends existed long before the coronavirus pandemic, which only aggravated the situation, causing food insecurity levels to spike in 2020 (up 1.5% from 2019). Food security is closely intertwined with other global problems of modernity, in particular, with the problem of climate change on Earth. In this regard, Russia’s role as a leading exporter of agro-food products, especially wheat, is great. The article considers the relationship between food security problems and climate change, analyzes the evolution of understanding of the food security problem and approaches to its solution. The factors affecting the state of food security in Russia are examines separately.